Energy conservation, emission reduction and win–win development of China's industry: 2013–2050 – MDI analysis framework based on directional distance function. Issue 17 (21st November 2016) - Chen, C.F.; Han, J.
ABSTRACT: As the biggest developing country, China faces the heavy pressure of energy conservation and emission reduction (ECER). China's industry takes first place in energy consumption and pollution emission among the industrial entities. How to get rid of China's industrial stagnant growth under the restriction of resources and environment, and find out the optimal path between ECER and industrial development is the main task of this study. The article adopts the historical data of China's industry from 2003 to 2012, establishes a managerial disposability intensity analysis framework based on the directional distance function, and designs four energy conservation scenarios and nine CO2 emission paths for a total of 36 kinds of alternative policy combinations to predict the win–win development and find the optimal path of industrial ECER from 2013 to 2050. Research shows that on the whole, industry will fail to achieve a win–win development in the future, while 6% growth rate of industrial output, 2.8% growth rate of energy consumption, and the peak of CO2 in 2040 is the most optimum path. At the same time, the feedbacks of ECER constraints on specific industrial sectors are different, there are 16 industrial sectors that can achieve win–win development in the future.